In vitro Shoot Proliferation through Cotyledonary Node and Shoot Tip Explants of Ficus religiosa L. - Hesami, Mohsen; Daneshvar, Mohammad Hosein; Lotfi, Amin (Plant Tissue Culture and Biotechnology, 2017)
Abstract not available Plant Tissue Cult. & Biotech. 27(1): 85-88, 2017 (June)